The selective leaching of copper from a gold–copper concentrate in glycine solutions - Oraby, E; Eksteen, Jacques (Elsevier, 2014)
The presence of copper minerals with gold is known to lead to many challenges during the cyanidation of gold ores, such as high consumption of cyanide with low gold extraction and undesirable impacts on gold recovery during the downstream processes. An alternative selective leaching process for copper minerals from copper–gold gravity concentrate (3.75% Cu, 11.6% Fe, 11.4%S and 0.213% Au) using alkaline glycine solutions was studied and evaluated. The lixiviant system containing glycine and peroxide showed that total copper dissolution of 98% was obtained in 48 h at ambient conditions and a pH of 10.5–11. The results show that 100% of chalcocite, cuprite, metallic copper, and about 80% of chalcopyrite in the concentrate were also dissolved. Pyrite remained intact during the leaching time and iron concentration in the final pregnant solution was found to be 12 mg/L when copper is solution is at 4745 mg/L, whilst the gold concentration was limited to 0.8 mg/L Au. QEMScan analysis indicated that unleached copper in the leach residue was mostly distributed amongst larger chalcopyrite grains and covellite.The effects of single versus two-stage leaching, pH, oxidant concentration, pulp density and glycine concentration on copper extraction rate and extent were explored